2018
DOI: 10.1590/s2179-975x0917
|View full text |Cite
|
Sign up to set email alerts
|

Is competition an interaction as relevant as predation for tropical planktonic cladocerans?

Abstract: Aim To test the relevance of competition and predation for the two most abundant and frequent cladoceran populations, the medium-sized Ceriodaphnia richardi Sars, 1901 and the large-sized Daphnia gessneri Herbst, 1967, in a tropical shallow lake. Methods Laboratory experiments and weekly samplings in the lake for a year were performed to evaluate: density fluctuations and reproduction; predation on juveniles and adults by larvae of Chaoborus brasiliensis Theobald, 1901; competitive interactions and possible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 44 publications
3
14
0
1
Order By: Relevance
“…Temporal variations of functional groups of rotifers in Lake Monte Alegre indicated the indirect effect of cladoceran predation by invertebrates, such as Chaoborus brasiliensis larvae and the aquatic mite, Krendowskia sp., in 2011-2012 41 . Predation pressure by invertebrates is generally higher in the warm season when their populations increased, resulting in declining cladoceran populations 29,41 . Consequently, there is a decrease in exploitative competition by cladocerans and the possibility of competitive exclusion when resources are limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal variations of functional groups of rotifers in Lake Monte Alegre indicated the indirect effect of cladoceran predation by invertebrates, such as Chaoborus brasiliensis larvae and the aquatic mite, Krendowskia sp., in 2011-2012 41 . Predation pressure by invertebrates is generally higher in the warm season when their populations increased, resulting in declining cladoceran populations 29,41 . Consequently, there is a decrease in exploitative competition by cladocerans and the possibility of competitive exclusion when resources are limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the composition and density of cladoceran species in Lake Monte Alegre are more evident in the warm season (spring and summer) than in the cool season, along with an increase in Chaoborus density (Arcifa et al, 2015). A sharp reduction in Ceriodaphnia density was observed in this season (Ferreira et al, 2018), while Diaphanosoma remained less abundant throughout the year in the limnetic zone (Ferreira, 2013). The laboratory experiments in the present study provide evidence that Chaoborus predation is of significant importance for lake grazers and that both cladoceran species, D. birgei and C. richardi, can be strongly affected by it, the first being the most affected species.…”
Section: Linking Experiments and Lake Datamentioning
confidence: 90%
“…Competition could be another important factor, but experiments using seston from the lake as food did not result in clear competition among cladocerans (Ferreira and Arcifa, in preparation), although it occurs when a laboratory alga was offered in limited concentrations. Experiments on competition between Daphnia gessneri and Ceriodaphnia richardi under food limitation showed that C. richardi was a superior competitor to D. gessneri (Ferreira et al, 2018). However, in the lake, the fluctuations of the populations of the two species indicated the prevalence of predation, because although there was a higher carbon concentration and a higher egg production per female in the warm season, their abundance was lower, particularly for C. richardi (Ferreira et al, 2018).…”
Section: Linking Experiments and Lake Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Ou seja, mesmo em densidades menores que outras presas, as presas maiores serão mais frequentemente escolhidas. Esta ideia levou à generalização de que alguns invertebrados aquáticos são predadores seletivos pelo tamanho das presas (Zaret 1980) Ferreira et al 2018). No entanto, esta elevada média em abril (215,9 ind/L) em relação a agosto (44,9 ind/L), está claramente influenciada pela densidade populacional de D. cf.…”
Section: Discussionunclassified